Impacts of COVID-19 in Breast Cancer: From Molecular Mechanism to the Treatment Approach - Stipp, Maria C.; Corso, Claudia Rita; Acco, Alexandra (Current Pharmaceutical Biotechnology, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has already infected more than 272 million people, resulting in 5.3 million deaths worldwide from COVID-19. Breast tumors are considered the world’s most commonly diagnosed cancer. Both breast cancer and COVID-19 share common pathogenic features, represented by inflammatory mediators and the potential of SARS-CoV-2 replication in metastatic cancer cells. This may intensify viral load in patients, thereby triggering severe COVID-19 complications. Thus, cancer patients have a high risk of developing severe COVID-19 with SARS-CoV-2 infection and a higher rate of complications and death than non-cancer patients. The present review discusses common mechanisms between COVID-19 and breast cancer and the particular susceptibility to COVID-19 in breast cancer patients. We describe the effects of chemotherapeutic agents that are used against this cancer, which should be considered from the perspective of susceptibility to SARS-CoV-2 infection and risk of developing severe events. We also present potential drug interactions between chemotherapies that are used to treat breast cancer and drugs that are applied for COVID-19. The drugs that are identified as having the most interactions are doxorubicin and azithromycin. Both drugs can interact with each other and with other drugs, which likely requires additional drug monitoring and changes in drug dosage and timing of administration. Further clinical and observational studies involving breast cancer patients who acquire COVID-19 are needed to define the best therapeutic approach when considering the course of both diseases.
Keywords: cytokine storm